Smart IoT Monitoring System for Pico-Hydropower Station Based on Permanent Magnet Generator with Radial Flux - Cumbajín, Myriam (2022)
We present the development of an Intelligent Internet of Things Monitoring System for a Pico-Hydropower Station based on a radial flux permanent magnet generator. The system mainly acquires the physical and electrical variables of the Pico-Hydropower Station located in the Ambato - Huachi - Pelileo irrigation channel, in the province of Tungurahua in Ecuador and then provides the information in real time on a Web page and stores it in a database. The IoT Monitoring System mainly provides information for the efficient management of the Pico-Hydropower Station. The IoT Monitoring system uses voltage, current, and Hall effect sensors that feed the information to an Arduino Uno development board. The data is then sent to a Raspberry PI development board, where it is displayed on a monitor screen at via VNC, they are published on the website and stored for further processing. The IoT Monitoring System is a convenient system to provide information on electricity production at any time and allows monitoring the appearance of any problems which is a valuable information to make the right decision when is required. So the system is a good contribution to maintenance management and smart cities of the future.